Search for photon-linelike signatures from dark matter annihilations with H.E.S.S. - Abramowski, A.; Acero, F.; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, A.; Barnacka, A.; Becherini, Y.; Tjus, J. Becker; Bernloehr, K.; Birsin, E.; et al. (Physical Review Letters, 2013)
Gamma-ray line signatures can be expected in the very-high-energy (E >100 GeV) domain due to self-annihilation or decay of dark matter (DM) particles in space. Such a signal would be readily distinguishable from astrophysical γ-ray sources that in most cases produce continuous spectra that span over several orders of magnitude in energy. Using data collected with the H.E.S.S. γ-ray instrument, upper limits on linelike emission are obtained in the energy range between ∼500 GeV and ∼25 TeV for the central part of the Milky Way halo and for extragalactic observations, complementing recent limits obtained with the Fermi-LAT instrument at lower energies. No statistically significant signal could be found. For monochromatic γ-ray line emission, flux limits of (2×107- 2×105) m2 s1 sr1 and (1×108-2×106) m2 s1 sr1 are obtained for the central part of the Milky Way halo and extragalactic observations, respectively. For a DM particle mass of 1 TeV, limits on the velocity-averaged DM annihilation cross section âŸ̈σvâŸ© reach ∼1027 cm3 s 1, based on the Einasto parametrization of the Galactic DM halo density profile. © 2013 American Physical Society.